Evident black hole-bulge coevolution in the distant universe. Issue 3 (2nd March 2019) - Yang(杨光), G; Brandt, W N; Alexander, D M; Chen(陳建廷), C-T J; Ni(倪清泠), Q; Vito, F; Zhu(朱飞凡), F-F
ABSTRACT: Observations in the local universe show a tight correlation between the masses of supermassive black holes (SMBHs; M BH ) and host-galaxy bulges ( M bulge ), suggesting a strong connection between SMBH and bulge growth. However, direct evidence for such a connection in the distant universe remains elusive. We have studied sample-averaged SMBH accretion rate (BHAR ) for bulge-dominated galaxies at z = 0.5–3. While previous observations foundBHAR is strongly related to host-galaxy stellar mass ( M ⋆ ) for the overall galaxy population, our analyses show that, for the bulge-dominated population, BHAR is mainly related to SFR rather than M ⋆ . ThisBHAR –SFR relation is highly significant, e.g. 9.0σ (Pearson statistic) at z = 0.5–1.5. Such aBHAR –SFR connection does not exist among our comparison sample of galaxies that are not bulge dominated, for which M ⋆ appears to be the main determinant of SMBH accretion. This difference between the bulge-dominated and comparison samples indicates that SMBHs only coevolve with bulges rather than the entire galaxies, explaining the tightness of the local M BH − M bulge correlation. Our best-fittingBHAR –SFR relation for the bulge-dominated sample isBHAR= SFR - (2.48± 0.05) (solar units). The best-fittingBHAR/SFR ratio (10 −2.48 ) for bulge-dominated galaxies is similar to the observed M BH / M bulge values in the local universe. Our results reveal that SMBH and bulge growth are in lockstep, and thus non-causal scenarios of merger averaging are unlikely the origin of the M BH − M bulge correlation. This lockstep growth also predicts that the M BH − M bulge relation should not have strong redshift dependence.